Synthesis of acicular α-Bi2O3 microcrystals by microwave-assisted hydrothermal method - Schmidt, Samara [UNESP]; Kubaski, Evaldo T.; Volanti, Diogo P. [UNESP]; Sequinel, Thiago; Bezzon, Vinicius D. N. [UNESP]; Tebcherani, Sergio M. (Taylor & Francis, 2019)
Materials based on bismuth(III) oxide are candidate to be used in optical and electronic devices because of their properties such as a variable band gap, photoconductivity, photoluminescence, high refractive index, and dielectric permittivity. These properties are dependent of several factors, e.g., present phases and crystal morphology. The microwave-assisted hydrothermal method (MAH) is a fast and efficient approach of synthesis to obtain semiconductor powders. However, the synthesis of monoclinic bismuth oxide (α-Bi2O3) with acicular morphology by MAH was not found in literature. In this paper, microcrystals of acicular α-Bi2O3 (monophasic) were successfully obtained by MAH using a synthesis temperature of 80°C for 0.5 h. X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron, and transmission electron microscopies showed the formation of a monoclinic structure (space group P21/c) with acicular morphology that grew along the [001] direction. The temperature and time necessary to synthetize acicular microcrystals were significantly lower than those found for acicular microcrystals obtained by conventional hydrothermal method.
Keywords: Bismuth(III) oxide microcrystal; crystal growth; hydrothermal method; microwave processing; powders: chemical preparation